Weather Information for Tribune - D. Bond; J. Slattery (Kansas Agricultural Experiment Station Research Reports, 2022)
Summary of 2021 weather for research conducted at the Tribune Kansas Agricultural Experiment Station field location.
Keywords: Tribune weather; 2021 weather; southwest Kansas weather; western Kansas weather